KARAKTERISTIK SUKU DALAM PENGUASAAN WILAYAH DAN POTENSI LOKAL: Perspektif Adat Saireri, Doberai, Dan Bomberai - Marit, Elisabeth Lenny (Universitas Papua, 2018)
This paper reveals the characteristics of the tribes in the Saireri, Doberai and Bomberai Adat territories of the Province of West Papua have a social-cultural view and value of nature (earth, land, sea, hamlet, gardens, forest, island) as follows: (1) economic character: as a medium that provides all the necessities and necessities of life, ranging fromfood, beverages, medicines, firewood and home-made materials; (2) cultural character: as mama, namely the party that gives birth and raises; is therefore Ã¢Â€ÂœlegitimateÃ¢Â€Â if the mother guarantees the life of all her children with the fertility and abundance of natural wealth; (3) religious character: associated and / or associated with the ancestors, spirits of their ancestors; (4) political character: part of the sovereignty of society. In the stages of human relationships with the environment, it can be shown that all aspects of culture, behavior and even the Ã¢Â€ÂœfateÃ¢Â€Â of human beings are influenced, determined and subject to the environment. In the life of the group there are forms of human life alliance arising as a result of climate, geography, and economic interactions. The three parts of the environment are also very determinant of the style of human tempramen.